An Overview of the Supramolecular Systems for Gene and Drug Delivery in Tissue Regeneration - Saketh Reddy Ranamalla; Alina Silvia Porfire; Ioan Tomuță; Manuela Banciu (MDPI AG, 2022)
Tissue regeneration is a prominent area of research, developing biomaterials aimed to be tunable, mechanistic scaffolds that mimic the physiological environment of the tissue. These biomaterials are projected to effectively possess similar chemical and biological properties, while at the same time are required to be safely and quickly degradable in the body once the desired restoration is achieved. Supramolecular systems composed of reversible, non-covalently connected, self-assembly units that respond to biological stimuli and signal cells have efficiently been developed as preferred biomaterials. Their biocompatibility and the ability to engineer the functionality have led to promising results in regenerative therapy. This review was intended to illuminate those who wish to envisage the niche translational research in regenerative therapy by summarizing the various explored types, chemistry, mechanisms, stimuli receptivity, and other advancements of supramolecular systems.